Towards pattern‐based architectures for event processing systems. (28th May 2013) - Bruns, Ralf; Dunkel, Jürgen
SUMMARY Recently, event processing (EP) has gained considerable attention as an individual discipline in computer science. From a software engineering perspective, EP systems still lack the maturity of well‐established software architectures. For the development of industrial EP systems, generally accepted software architectures based on proven design patterns and principles are still missing. In this article, we introduce a catalog of design patterns that supports the development of event‐driven architectures (EDAs) and complex EP systems. The design principles originate from experiences reported in publications as well as from our own experiences in building EP systems with industrial and academic partners. We present several patterns on different layers of abstractions that define the overall structure as well as the building blocks for EP systems. Architectural patterns that determine the top‐level structure of an EDA can be distinguished from design patterns that specify the basic mechanisms of EP. The practical application of the catalog of patterns is described by the pattern‐based design of a sample EDA for a sensor‐based energy control system. Finally, we propose a coherent and general reference architecture for EP derived from the proposed patterns.Copyright © 2013 John Wiley & Sons, Ltd.